The Effect of Hypoxic Exercise Combined with Crocodile Blood Supplementation on Aerobic Capacity and Hematological Variables in Athletes - Worrawut Thuwakum; Apiwan Manimmanakorn; Win Chaeychomsri; Jindawan Siruntawineti; Sasithorn Sukjit (OVS LLC, 2024)
Study purpose. This study aimed to compare the effects of hypoxic exercise combined with crocodile blood supplementation on hematological and maximum oxygen consumption parameters in soccer players.  Materials and methods. This study included 39 male soccer players aged 21.69 ± 1.98 years who were randomized to three groups. All groups performed the same training program, which comprised treadmill exercise at 70%-75% of maximum heart rate for 7 weeks with sessions of 30 min/day and 3 days per week. The first group was the control placebo group (CG, n = 13), the second group received one capsule per day (60 mg) of a freeze-dried crocodile blood supplement (SUP, n = 13), and the third group received the freeze-dried crocodile blood supplement and performed the training program under hypoxic conditions (H-SUP, n = 13, FiO2 = 16.3%). A hematological evaluation was conducted and maximal oxygen uptake (VO2max) was measured using the Bruce protocol treadmill test.  Results. The H-SUP group demonstrated significantly higher erythropoietin (EPO) levels (14.40 ± 2.41 mIU/mL) compared to the SUP group (11.50 ± 2.08 mIU/mL) and CG (12.01 mIU/mL) after the intervention. From pre- to post-intervention, VO2max significantly increased in the H-SUP (Pre: 45.63 ± 4.75, Post: 49.33 ± 5.81) and SUP groups (Pre: 44.59 ± 4.75, Post: 47.30 ± 5.68) but not in the CG.  Conclusions. This study reveals that a combination of freeze-dried crocodile blood supplementation and hypoxic exercise causes hematological alterations, particularly the activation of EPO secretion, and increases VO2max in soccer players.